Mechanobiological model of bone tissue regeneration on scaffolds (2016)
Abstract. Scaffolds are one of the most used strategies of tissue engineering in the treatment of bone defects; they help to meet the mechanical function of load bearing that bones play in the human body. The design and fabrication of scaffolds made of biodegradable polymers is of particular interest. As they erode, scaffolds leave empty space that can be occupied by new regenerated bone. For the scaffold to meet the clinical requirements, it is vital to pay attention to the design of the geometry of the implant’s porous structure, the manufacturing technique, and performance of the scaffold once implanted. To enter in this field, the development of a mechanobiological model of bone regeneration process on scaffolds is presented here. In this thesis, we are obtaining an irregular three-dimensional pattern using a reaction-diffusion. Degradation of a representative volume element of the scaffold is studied due to a hydrolysis process, and the regeneration of bone tissue on the scaffold is modeled. Finally, some scaffolds are manufactured using additive manufacturing to study its mechanical properties. In conclusion, it is found that the proposed geometry can be useful for the design of scaffolds and may be considered for future designs and experimental work in order to develop biodegradable scaffolds similar to trabecular bone.